Hostile Environment : The Political Betrayal of Sexually Harassed Women - Mink, Gwendolyn (Book collections on Project MUSE., 2018)
According to some of President Clinton's feminist supporters, his alleged behavior toward Paula Jones did not constitute sexual harassment because he had taken "no" for an answer. Others insisted that Jones could not have been harassed because the president did not punish her for refusing him. During the impeachment debate, many feminists defended the president on the grounds that his alleged lies in the Jones case were "just about sex" and therefore insignificant. In the most publicized sexual harassment case to date, longtime proponents of sexual harassment law raised the political and legal thresholds for taking sexual harassment seriously.In a passionate defense of the rights of sexually harassed women, Gwendolyn Mink warns that the president's supporters have undermined our sexual harassment laws. Hostile Environment is her provocative account of the harm being done to these laws and her warning that the laws themselves are worthless if few women dare to use them.Correcting many common misapprehensions, Mink explains sexual harassment as a legal concept and charts its judicial and legislative history. She shows the many important contributions feminists have made to the development of sexual harassment law. She also, however, develops a stringent critique of feminist responses to the president's lies in the Jones case. Sometimes scathing, Hostile Environment provides a fresh perspective on the recent politics of sexual harassment. It also provides a highly personal perspective. First-hand knowledge of the injuries caused by sexual harassment and its aftermath has left Mink with an abiding interest in this volatile issue and with a desire to safeguard the rights of sexually harassed women--especially the most economically vulnerable among them.